2023
DOI: 10.1002/pc.27327
|View full text |Cite
|
Sign up to set email alerts
|

In situ resin‐injection approach for repairing barely visible impact damaged carbon‐fiber reinforced epoxy laminates: Optimizing the repair parameters using Taguchi method

Abstract: A new portable resin injection device has been developed to repair barely visible impact damage (BVID) in carbon fiber reinforced polymer (CFRP) laminates. Repair was conducted on damaged 16‐ and 24‐ply laminates at two different ambient pressures, that is, atmospheric pressure and vacuum, using three different adhesive types, that is, neat epoxy, epoxy blended with respective halloysite nanotubes (E1HNT) and carbon nanotubes (NF100). The repair effectiveness was assessed by infrared thermography and in‐plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…During the application of resin‐injection, with respect to the shear thinning effect, low shear rates indicated that lower pressure is required to inject the adhesive into the cracks, while higher shear rates suggested the need for higher pressure to inject the adhesive into the cracks 18 . It is crucial to note that injecting adhesive into the crack of CFRP structure at high pressure should be avoided, as it may lead to crack expansion and further propagations of damage 17,60 . Therefore, for effective infiltration of the adhesive into the crack network, it is essential for the adhesive to exhibit low viscosity at low shear rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the application of resin‐injection, with respect to the shear thinning effect, low shear rates indicated that lower pressure is required to inject the adhesive into the cracks, while higher shear rates suggested the need for higher pressure to inject the adhesive into the cracks 18 . It is crucial to note that injecting adhesive into the crack of CFRP structure at high pressure should be avoided, as it may lead to crack expansion and further propagations of damage 17,60 . Therefore, for effective infiltration of the adhesive into the crack network, it is essential for the adhesive to exhibit low viscosity at low shear rates.…”
Section: Resultsmentioning
confidence: 99%
“…18 It is crucial to note that injecting adhesive into the crack of CFRP structure at high pressure should be avoided, as it may lead to crack expansion and further propagations of damage. 17,60 Therefore, for effective infiltration of the adhesive into the crack network, it is essential for the adhesive to exhibit low viscosity at low shear rates. (d) The neat DGEBA adhesive and adhesive with 1, 3, and 5 wt% HNTs are suitable for repairing damaged CFRP structures.…”
Section: Rheological Properties Of Adhesivementioning
confidence: 99%
“…Numerous studies have been conducted on quasistatic indentation testing and the detection of local damage in polymer matrix composites. 15,16 This damage may manifest itself in a variety of ways, including cracking, debonding, and breaking, all of which have an impact on the composite's strength and stiffness. Jayababu et al 17 examined the indentation resistance of UD and CP GFRP laminates.…”
Section: Introductionmentioning
confidence: 99%